2022
DOI: 10.1186/s12943-022-01500-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of m6A RNA methylation in cancer metabolism

Abstract: Metabolic reprogramming is one of the main characteristics of malignant tumors, which is due to the flexible changes of cell metabolism that can meet the needs of cell growth and maintain the homeostasis of tissue environments. Cancer cells can obtain metabolic adaptation through a variety of endogenous and exogenous signaling pathways, which can not only promote the growth of malignant cancer cells, but also start the transformation process of cells to adapt to tumor microenvironment. Studies show that m6A RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
229
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(229 citation statements)
references
References 169 publications
(169 reference statements)
0
229
0
Order By: Relevance
“…Notably, hypoxia and tumor growth form a mutually positive feedback loop. Tumor cell proliferation leads to excessive oxygen depletion and promotes a hypoxic environment in TME, which, in turn, provides conditions suitable for tumorigenesis and metastasis through multiple modalities including proliferation, differentiation, and drug resistance [ 23 , 27 ]. Cell response to hypoxia is mainly controlled by hypoxia-inducible factors (HIF), heterodimeric helix-loop-helix proteins composed of O 2 -labile alpha and constitutively expressed beta subunits (HIF1α, HIF2α, and HIF-1β), involved in coordinating the regulation of numerous mechanisms that enable tumor cells to adapt to the hostile environment [ 28 ].…”
Section: A Methylation and Hypoxia In Tmementioning
confidence: 99%
“…Notably, hypoxia and tumor growth form a mutually positive feedback loop. Tumor cell proliferation leads to excessive oxygen depletion and promotes a hypoxic environment in TME, which, in turn, provides conditions suitable for tumorigenesis and metastasis through multiple modalities including proliferation, differentiation, and drug resistance [ 23 , 27 ]. Cell response to hypoxia is mainly controlled by hypoxia-inducible factors (HIF), heterodimeric helix-loop-helix proteins composed of O 2 -labile alpha and constitutively expressed beta subunits (HIF1α, HIF2α, and HIF-1β), involved in coordinating the regulation of numerous mechanisms that enable tumor cells to adapt to the hostile environment [ 28 ].…”
Section: A Methylation and Hypoxia In Tmementioning
confidence: 99%
“…Coupled with the limitation of the local space, the supply of oxygen and nutrients is reduced, and it is easy to form a hypoxic microenvironment in the local tumor ( 32 ). Although its growth can be inhibited to a certain extent through energy metabolism, for some malignant solid tumors, hypoxia can stimulate tumor cell metabolism and changes in malignant behavior, providing a suitable environment for the survival of pancreatic cancer cells ( 33 ). Studies have shown that the hypoxic microenvironment is a key factor in tumor progression, immune escape, and treatment tolerance ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA N6-methyladenosine (m6A) modification as the most abundant mRNA modification has attracted much attention recently [ 57 ]. The modification of m6A plays a role in the regulation of occurrence and development of tumors by modulating expressions of key genes, becoming the hot spot of research recently [ 58 ].…”
Section: Discussionmentioning
confidence: 99%